2023
DOI: 10.3390/children10010106
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Barriers to Rapid Whole Genome Sequencing in Pediatrics: Michigan’s Project Baby Deer

Abstract: The integration of precision medicine in the care of hospitalized children is ever evolving. However, access to new genomic diagnostics such as rapid whole genome sequencing (rWGS) is hindered by barriers in implementation. Michigan’s Project Baby Deer (PBD) is a multi-center collaborative effort that sought to break down barriers to access by offering rWGS to critically ill neonatal and pediatric inpatients in Michigan. The clinical champion team used a standardized approach with inclusion and exclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
5
15
0
Order By: Relevance
“…The high yield of broad exome sequencing that we report in critically ill adults can be put in the context of a number of recent similar studies of broad exome/genome sequencing in the critically ill pediatric and neonatal patient populations that have reported diagnostic rates of 21-38%. 2–4,9,10 The diagnostic yield that we report here is essentially the same as those reported in these studies, suggesting that critical illness is a strong predictor of Mendelian disease across the life span. Importantly, many of these studies found significant cost savings and important changes in management due to rapid exome/genome sequencing.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The high yield of broad exome sequencing that we report in critically ill adults can be put in the context of a number of recent similar studies of broad exome/genome sequencing in the critically ill pediatric and neonatal patient populations that have reported diagnostic rates of 21-38%. 2–4,9,10 The diagnostic yield that we report here is essentially the same as those reported in these studies, suggesting that critical illness is a strong predictor of Mendelian disease across the life span. Importantly, many of these studies found significant cost savings and important changes in management due to rapid exome/genome sequencing.…”
Section: Discussionsupporting
confidence: 84%
“…[2][3][4][5][6][7][8] Expansion of rapid genomic tes1ng to all cri1cally ill pediatric pa1ents replicates these clinical and financial implica1ons. [9][10][11] However, despite the well-documented benefits in pediatric popula1ons, genomic tes1ng is not rou1nely offered during the care of cri1cally ill adults.…”
Section: Introduconmentioning
confidence: 99%
“…WINGS has demonstrated that it is possible to provide reliable rWGS for acutely unwell infants and children in the NHS. WINGS provides timely diagnoses within a time frame that can alter patient care, as reported in other smaller healthcare or research settings 3 20 23 24. The overall and phenotype-specific diagnostic yields are similar to previously published reports 1–3 6 25 26.…”
Section: Discussionsupporting
confidence: 76%
“…Also, although it is clear there has been a direct effect on acute clinical management for some patients, the report has not locally assessed the impact on patient care or morbidity, or the economic benefits of rWGS in Wales. This is because previous research-based reports have already demonstrated the benefits of rWGS for patients and their families3 23 24 32 and it was outside the scope of this clinical review. Additionally, economic analyses often require large cohorts, making them more difficult in the NHS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation